Application of optical flow methods to aerated skimming flows above triangular and trapezoidal step cavities. Issue 4 (4th July 2019) - Zhang, Gangfu; Chanson, Hubert
ABSTRACT: Stepped chutes are built to provide safe flood passage in dams. The steps are associated with strong turbulence generation, which allow air to be entrained from the free surface. The present work adopts a non-intrusive local optical flow technique to examine the effects of partial cavity blockage on the mean and turbulent properties in aerated skimming flows in two large-size stepped chute models. The partial cavity blockage was found to be associated with decreased mean velocities in the overflow. The step edge was identified as the most significant source of turbulent production. General increases in turbulence levels and large scale turbulent motions were identified for the partially blocked cavities, which could be linked to a reduction in mutual sheltering between adjacent roughness elements. It was implied that the cavity blockage might have some effects on the velocity gradient fluctuations.